The Historical Significance of Theater Troops and the Works of National Intellectuals and Dramaturgs in the Kashkadarya Oasis During the Soviet Period - Axmatov Abdulla (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
This article analyzes the fundamental changes that occurred in the development of theatrical art in Uzbekistan with the establishment of Soviet power based on historical sources. The study covers the processes of subordinating the theater to ideological tasks in 1918–1930, the formation of amateur and semi-professional troupes, and the transfer of theater activities to centralized management by the People's Commissariat of Education. The contribution of such creators as Abdulla Kadirov-Tanburiy, Ikroma Boltaeva, and Majid Mamatov to the formation and development of the musical drama theater in the Kashkadarya oasis is analyzed separately.